THEORETICAL-PHILOSOPHICAL ANALYSIS OF HISTORICAL-CULTURAL HERITAGE (Academicia Globe: Inderscience Research, 2023)
This article reveals the scientific and socio-philosophical foundations of the historical-cultural heritage, its special reality and phenomenon related to the past of the people, the nation, life and epistemological experiences, and material and spiritual wealth and artifacts. It is explained that the historical-cultural heritage is a special phenomenon related to the social existence of the people, the nation, epistemological researches and experiences, creative activities aimed at changing the world. Theoretical conclusions on effective use of intellectual potential and positive experiences in historical-cultural heritage in innovative development are given.